The Nature of Airport Brand Associations - Henderson IL; Tsui KWH; Ngo T; Gilbey A; Avis M (MDPI (Basel, Switzerland), 2024)
This study examines the nature of brand associations that air travellers form with airports and which associations are important when choosing between airports. Using semi-structured qualitative interviews, this study collected information about 240 participants’ most recent trips using air travel, encompassing 642 airport visits and 88 airports worldwide. The associations that participants made with the airports they travelled through were collected, as well as the sorts of associations that are important for choosing between airports and why those associations are important. The data were analysed using thematic analysis, revealing 13 themes each for airport brand associations and important associations for choosing between airports and 14 themes for reasons why those associations were important. Single-sample t-tests reveal that each of these themes has a different effect size in terms of its effect on airport brand association formation and its effect on attitudinal brand choice. This study contributes to the air transport and tourism literature by providing a detailed account of which associations air travellers form with airports and which are used for choosing between airports by contextualising these findings by viewing airports as compound brands. Managerial implications are also provided along with avenues for future research.
Keywords: travel experience; travel behaviour; airport management; brand choice; brand associations; airport choice